2012
DOI: 10.1504/ijise.2012.046651
|View full text |Cite
|
Sign up to set email alerts
|

Selection of industrial robots using compromise ranking method

Abstract: Selection of an industrial robot for a specific engineering application is one of the most challenging problems in real time manufacturing environment. This has become more and more complicated due to increasing complexity, advanced features and facilities that are continuously being incorporated into the robots by different manufacturers. The decision maker needs to select the most suitable industrial robot in order to achieve the desired output with minimum cost and specific application ability. This paper m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 15 publications
1
9
0
2
Order By: Relevance
“…Chatterjee and Chakraborty [2] obtained this value as 1.00 with a perfect correlation. The correlation coefficient value (0.96 in our study) for TOPSIS and VIKOR methods was obtained as 0.83 in the study of Athawale et al [25]. It can be concluded that the correlations acquired between these methods are generally in acceptable range.…”
Section: Vikor Methodssupporting
confidence: 62%
See 1 more Smart Citation
“…Chatterjee and Chakraborty [2] obtained this value as 1.00 with a perfect correlation. The correlation coefficient value (0.96 in our study) for TOPSIS and VIKOR methods was obtained as 0.83 in the study of Athawale et al [25]. It can be concluded that the correlations acquired between these methods are generally in acceptable range.…”
Section: Vikor Methodssupporting
confidence: 62%
“…The two Euclidean distances for each alternative are computed as given in Eqs. (25) and (26), respectively:…”
Section: Topsis Methodsmentioning
confidence: 99%
“…Devi (2011) extended VIKOR method in intuitionistic fuzzy environment for solving MCDM problems in the area of robot selection. Athawale et al (2012) applied VIKOR method for evaluating and ranking of industrial robots. Karsak et al (2012) presented a decision model based on fuzzy linear regression for industrial robot selection.…”
Section: Introductionmentioning
confidence: 99%
“…Penelitian [1], sistem dibuat untuk aplikasi industri desainer produk sebagai pilihan material yang didasarkan pada properti mekanik dan kimia. Hasil yang akan dicapai solusi ideal dalam melakukan pemilihan bahan dengan memperhitungkan nilai resiko kegagalan [2].…”
unclassified
“…Penelitian [2], sistem pendukung keputusan yang dibuat untuk modifikasi pada klasifikasi pembagian tanah Berdasarkan Kerentanan Daerah Aliran Sungai (DAS). Berbagai saluran dari tanah di sekitar DAS memiliki berbagai tingkat kerentanan lingkungan.…”
unclassified